2014
DOI: 10.1111/cas.12473
|View full text |Cite
|
Sign up to set email alerts
|

Multicenter retrospective analysis of systemic chemotherapy for advanced neuroendocrine carcinoma of the digestive system

Abstract: This study analyzed outcomes of systemic chemotherapy for advanced neuroendocrine carcinoma (NEC) of the digestive system. Clinical data from 258 patients with unresectable or recurrent NEC of the gastrointestinal tract (GI) or hepato-biliary-pancreatic system (HBP), who received chemotherapy, were collected from 23 Japanese institutions and analyzed retrospectively. Patients had primary sites in the esophagus (n = 85), stomach (n = 70), small bowel (n = 6), colorectum (n = 31), hepato-biliary system (n = 31) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
203
1
5

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 202 publications
(238 citation statements)
references
References 25 publications
13
203
1
5
Order By: Relevance
“…9,12 In Japan, combination chemotherapy using platinum plus irinotecan is also used. 13 However, no satisfactory survival rates have been achieved in these cases yet. 9,13 In this way, there is significant difference between G1, G2, and G3 cases on therapeutic strategy and survival duration.…”
Section: X190mm (96 X 96 Dpi)mentioning
confidence: 97%
See 1 more Smart Citation
“…9,12 In Japan, combination chemotherapy using platinum plus irinotecan is also used. 13 However, no satisfactory survival rates have been achieved in these cases yet. 9,13 In this way, there is significant difference between G1, G2, and G3 cases on therapeutic strategy and survival duration.…”
Section: X190mm (96 X 96 Dpi)mentioning
confidence: 97%
“…13 However, no satisfactory survival rates have been achieved in these cases yet. 9,13 In this way, there is significant difference between G1, G2, and G3 cases on therapeutic strategy and survival duration. Therefore, the identification of pathological grade is very important for unresectable case to be treated appropriately.…”
Section: X190mm (96 X 96 Dpi)mentioning
confidence: 97%
“…Chemotherapeutic regimens, including cisplatin, irinotecan, etoposide, doxorubicin and vincristine have been reported. Large-scale retrospective analyses of advanced gastrointestinal and pancreatic neuroendocrine carcinoma by a Japanese group demonstrated that irinotecan plus cisplatin and etoposide plus cisplatin are the most commonly used regimens (16).…”
Section: Discussionmentioning
confidence: 99%
“…Kulke et al (18) reported a very low response rate to cisplatin plus irinotecan for extra-pulmonary NETs, however, Okita et al (10) reported the response rate to cisplatin plus irinotecan for gastric poorly differentiated NEC was 75%. Large -scale retrospective analyses for advanced neuroendocrine carcinoma of the digestive system by Japanese group demonstrate that irinotecan plus cisplatin (IP) and etoposide plus cisplatin (EP) are the most commonly used regimens (19). IP was the most commonly selected regimen, especially for the gastrointestinal tract in the Japanese study (19), while EP was the most commonly selected regimen in the Nordic study (20).…”
Section: Discussionmentioning
confidence: 99%
“…Large -scale retrospective analyses for advanced neuroendocrine carcinoma of the digestive system by Japanese group demonstrate that irinotecan plus cisplatin (IP) and etoposide plus cisplatin (EP) are the most commonly used regimens (19). IP was the most commonly selected regimen, especially for the gastrointestinal tract in the Japanese study (19), while EP was the most commonly selected regimen in the Nordic study (20). The response rate of IP was slightly better than that of EP for the treatment of NEC, even after adjusting patient background by multivariate analysis.…”
Section: Discussionmentioning
confidence: 99%